Technical Application and Teaching Research Optimization of Civil Engineering Detailed Design Driven by BIMMAKE - Qin, Zhengding (Education Insights, 2026)
To address the challenges in traditional civil engineering detailed design, such as insufficient three-dimensional spatial representation, poor technical implementability, and ineffective multidisciplinary collaboration, and to align with the construction industry's demand for technical talents driven by digital transformation, this paper takes the BIMMAKE software as the core technical platform. It systematically analyzes its core technical application pathways in civil engineering detailed design, focusing on the technical optimization logic in key scenarios like secondary structures, steel reinforcement joints, and formwork configuration. By integrating teaching practices, an integrated system of "technology empowerment-design implementation-teaching-research collaboration" is constructed. Through deepening the integration of technology and design, targeted teaching-research optimization strategies are proposed. This aims to establish a teaching model that aligns with industry technological advancements, providing technical support and practical guidance for the reform of digital detailed design education in civil engineering, thereby fostering the cultivation of versatile design talents proficient in cutting-edge technologies.